Preparation Micro-Filtration Ceramic Membrane from Natural Zeolite for Procion Red MX8B and Methylene Blue Filtration - Dyah Choiriyah; Esfi Riandini; Arinta Wulandari (ALCHEMY Jurnal Penelitian Kimia, 2015)
The study of ceramic membrane fabrication from natural zeolite and its utilization for filtration of procion red MX8B and methylene blue has been investigated. The purposes of this study are to determine the effect of pressure on membrane permeability and selectivity and utilize natural zeolite as ceramic membranes procion red MX8B and methylene blue filtration. The membrane was prepared by metide press pellets and then calcined at 850 oC. The membranes were characterized by mechanical test, flux and rejection of dye. The compression test of the membrane found the values of 1369.178 psi in dry conditions to 1388.933 psi in wet conditions. The flux test found that the higher the pressure applied, the flux was increase. However, the high pressure also decreased the selectivity. Rejection test found that the rejection of methylene blue filtration up to 70 %. Meanwhile, procion red MX8B filtration has rejectivity less than 20 %.